Side effects after COVID-19 vaccination: a comparison between the most common available vaccines in Iran - Davood Yadegarynia; Shabnam Tehrani; Fahimeh Hadavand; Shahnam Arshi; Zahra Abtahian; Amirreza Keyvanfar; Azar Darvishi; Afshin Zarghi; Latif Gachkar; Ilad Alavi Darazam; Mohammad Farahbakhsh (Iranian Journal of Microbiology, 2023)
Background and Objectives: Since the coronavirus disease 2019 (COVID-19) pandemic began, several vaccines have been manufactured to subside it. This study aimed to determine the prevalence of side effects after injecting common COVID-19 vaccines available in Iran. Materials and Methods: This cross-sectional study was accomplished on Shahid Beheshti University of Medical Sciences (Tehran, Iran) employees during January and September 2022. Eligible participants were selected based on the simple random method and interviewed about side effects after injecting COVID-19 vaccine. Results: The mean age of 656 participants was 38.03 ± 9.53 years, and 453 (69.1%) were female. The prevalence of post-vaccination side effects was higher after receiving the first dose (53.2%) than the second (35.9%) and third (49.4%) doses. Across all three vaccine doses, the overall proportion of side effects was higher following AstraZeneca than the others. The most common side effect after the first dose of the vaccine was myalgia (41.9%), followed by fever (36.6%), chills (31.6%), local reactions (27.0%), headache (25.5%), and sweating (21.6%). People experienced mainly myalgia (23.3%) and fever (20.3%) after injecting the second dose of the vaccine. Additionally, the participants had myalgia (37.2%), fever (30.8%), chills (29.2%), local reactions (26.0%), and headache (24.4%) after the third dose of the vaccine. Conclusion: AstraZeneca had a higher proportion of post-vaccination adverse effects than Sputnik V, Pastocovac, and Sinopharm. The most common side effects were flu-like syndrome and local reactions at the injection site. Furthermore, people rarely experienced life-threatening side effects. Thus, the available COVID-19 vaccines in Iran are safe.